Surgical resection of primary tumour improves aerobic performance in colorectal cancer - Williams, John P.; Nyasavajjala, Sitaramachandra M.; Phillips, Beth E.; Chakrabarty, M.; Lund, Jonathan N. (Elsevier, 2014)
Background